Recognition of Failure Mode of Slope Block Failure Mode in Zhouning Pumped Storage Station Based on Stereographic Projection Method - KANG Zhiliang; ZHOU Shuntian; ZHU Yongsheng; CHU Weijiang; PAN Bing (Renmin Zhujiang, 2020)
Deformation and failure of rock slope are mainly controlled by structural planes developed in rock mass. The stereographic projection method is used to analyze the failure modes of rock slope, which can easily determine the combination relationship between structural planes and identify the failure risk mode of typical block. Based on the geological and engineering conditions of the slope at the lower reservoir site of Zhouning Pumped Storage Station, this paper predicts and analyzes the failure mode of random block of the slope is predicted and analyzed by the stereographic projection method. The results show that the slope has the structural plane condition for block failure, and the plane slip and wedge instability are the main failure modes that may occur during the construction period. The rationality and feasibility of the stereographic projection method for predicting the failure mode of the slope are verified by the on-site failure performance of the rock mass during the construction period.